1985
DOI: 10.1111/j.1365-2141.1985.tb02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporin‐induced immune neutropenia

Abstract: Neutropenia is an occasional complication of treatment with cephalosporin antibiotics. This report describes two patients who had neutropenia while receiving high doses of cephalosporins. The neutrophil counts returned to normal after stopping the drug, and cephalosporin-dependent neutrophil antibodies were demonstrated in both cases, using the granulocyte immunofluorescence test. In one patient, the immune neutropenia appeared to be due to a drug adsorption mechanism similar to penicillin-induced haemolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…prolonged treatment or high dose, progressive decrease in neutrophil counts…), the usual absence of clinical signs of hypersensitivity and the inconsistent detection of specific beta‐lactam‐induced antineutrophil antibodies. By contrast, an immune‐mediated reaction was considered in patients positively tested for the presence of drug‐dependent antibodies such as cefotaxime and cefuroxime . Also in keeping with an immune mechanism, one study involving 13 patients with beta‐lactam induced neutropaenia found a positive leucocyte microagglutination test in 8 of the 9 tested patients .…”
Section: Discussionmentioning
confidence: 99%
“…prolonged treatment or high dose, progressive decrease in neutrophil counts…), the usual absence of clinical signs of hypersensitivity and the inconsistent detection of specific beta‐lactam‐induced antineutrophil antibodies. By contrast, an immune‐mediated reaction was considered in patients positively tested for the presence of drug‐dependent antibodies such as cefotaxime and cefuroxime . Also in keeping with an immune mechanism, one study involving 13 patients with beta‐lactam induced neutropaenia found a positive leucocyte microagglutination test in 8 of the 9 tested patients .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of rash and agranulocytosis/neutropenia is intriguing for being an immune reaction. Antibodies to b-lactams have been demonstrated in DIAG patients as well as inhibition of colony growth in vitro by b-lactams [66][67][68].…”
Section: Immunologicalmentioning
confidence: 99%
“…The mechanism of the disorder, that is, toxic [5][6][7] or immune [8,9] mediated or both [10], is not fully understood. Our data do not afford to any conclusion regarding this question.…”
Section: Discussionmentioning
confidence: 99%